The Effect of Digitalization on Marine Ecosystem Alignment and the Role of Technology in Natural Resource Management in Sulawesi - Utomo, Bekti; Fildansyah, Rully (Westscience Press, 2024)
This study aims to review the impact of digitalization on marine ecosystem management with a specific focus on Sulawesi, Indonesia. It explores how advanced technologies such as remote sensing, Geographic Information Systems (GIS), machine learning, and blockchain are revolutionizing the monitoring, predictive capabilities, and sustainability practices in marine resource management. The review highlights both the transformative potential of these technologies and the associated challenges including infrastructural limitations, skill gaps, and the lagging adaptation of policy frameworks. The integration of traditional ecological knowledge (TEK) with modern digital tools is emphasized as a critical approach for enhancing the effectiveness and acceptability of technological interventions in marine conservation efforts. The findings suggest that while digital tools offer substantial benefits for ecosystem management, their full potential can only be realized through strategic solutions to overcome existing barriers, fostering an inclusive approach that combines innovation with traditional practices. This review contributes to the understanding of digitalization's role in marine ecosystem sustainability and provides a foundation for future research directions.